The Horto-Baratinha itabirite-hosted iron ore: A basal fragment of the Espinhaço basin in the eastern São Francisco Craton - Silveira Braga, F.; Rosière, C.; Schneider Santos, J.; Hagemann, S.; McNaughton, Neal; Valle Salles, P. (Pergamon, 2019)
The Horto-Baratinha (HBD) iron ore deposit is located at the eastern border of São Francisco Craton, comprising BIF-hosted high-grade bodies (>60 wt.% Fe) associated with polydeformed quartz-mica-schists, amphibole-schist of Statherian maximum deposition age, enclosed by Statherian granitoids of the Borrachudos Suite and Neoarchean gneiss. All the sequence is crosscut by undeformed dikes and sills of pegmatitic bodies probably formed during Late Ediacaran-Cambrian. The metasedimentary sequence is stratigraphically correlatable with the Orosirian-Statherian Serra da Serpentina and Serra de São José Groups that comprise the basal units of the Espinhaço Supergroup and was intensively segmented into distinct tectonic blocks. The sedimentary/diagenetic bedding of the metamorphosed BIF (itabirite) is generally transposed by an axial planar schistosity. The lamellar hematite from itabirite is the oldest iron oxide generation, which was formed during the syn-deformational stage, parallel-oriented to the rock foliation. The (keno)magnetite grains from itabirite, iron ore and pegmatite bodies developed as idioblasts that grew over the foliation formed during late and post-deformational stages. Magnetite oxidizes subsequently to martite and granular hematite. Coarse lamellar hematite crystals randomly oriented in the border of the pegmatitic bodies also formed during the post-deformational stage due to hydrothermal reaction with itabirite. The country rocks have undergone at least three stages of deformation developed during the syn-collisional and late-collisional (Ediacaran to early-Cambrian) phases of the Brasiliano Orogeny: stage 1 with the development of a pervasive foliation (S1), parallel to axial plane to tight folds and transposition of all sedimentary structures; stage 2 with folding of S1; stage 3 with refolding of S1. Both fold systems interfere with each other making up a dome and basin refolding shape. During the late-collisional (Ediacaran to early-Cambrian) and post-collisional/gravitational collapse (Cambrian) the sequence was intruded by anatectic pegmatitic bodies, which are part of the Eastern Brazilian Pegmatite Province, one of the most significant pegmatitic regions worldwide. The fluid related with these intrusions could be related with the Si leaching, crystallization of magnetite and granular hematite, and consequent formation of high-grade iron bodies.